Wzorzec gatunkowy a przekład specjalistyczny (analiza wybranych mechanizmów upraszczania języka w polskiej i włoskiej ulotce dla pacjenta) - Pronińska, Aleksandra (Acta Universitatis Lodziensis. Folia Linguistica, 2013)
The patient information leaflet is a specialized text of codified character. Its genre pattern, as defined in legal norms, includes all the genre-pattern aspects specified by Maria Wojtak, i.e. structural, cognitive (thematic), pragmatic and stylistic. Within the stylistic component it is possible to distinguish different language and stylistic devices the aim of which is to facilitate the reader’s understanding of the text. The article focuses on the analysis of one of these mechanisms, namely metatextual annotations in the form of parenthesis (inclusion) provided in Polish and Italian, and intended to facilitate (the reader’s) understanding of the text with regard to specialized terminology. Carrying out the comparison resulted in doubts whether numerous metatextual parenthetic annotations really fulfill their function.